Cycling and sustainability - Parkin, John (Emerald, 2012)
The book explores the reasons for difficulties in making cycling mainstream in many cultures, despite its claims for being one of the most sustainable forms of transport. The topic is looked at from the varying perspectives of people, the environment and the economy with multi-disciplinary contributions from the UK, Denmark, the Netherlands, Sweden, Spain, Gemany, Australia, China and USA. Initially it examines the cultural development of cycling in countries with high use and the differences in use between different sub-groups of the population. It then explores issues of urban form, and the attributes of the network and the system for appropriately accommodating cycle users. Cross-cultural issues are once again investigated through an exposition of research in developing countries and the environment in which scheme promoters and users operate. The book draws to a close with an exploration of state-of-the-art thinking on demand model.
Includes index.
Keywords: Transportation -- General.; Transport: general interest.; Sustainability.; Bicycle commuting.; Bicycle lanes.; Cycling -- Social aspects.; elektronické knihy; electronic books